Environmental influences on polyphosphate accumulation in microalgae : an investigation into species differences and transcriptional responses : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Engineering at Massey University, Manawatū, New Zealand - Cliff, Alexander (Massey University, 2022)
Many species of microalgae can store phosphorus (P) as polyphosphate (polyP) granules during the process of ‘luxury uptake’, a term describing intracellular P accumulation above levels required for normal metabolism (0.2 – 1% P by dry weight). Environmental conditions can influence P luxury uptake but it is not known whether the effects of environmental conditions on luxury P uptake are the same for all microalgae or whether all microalgae can in fact store P as polyP. The broad aim of the work described in this thesis was to extend the current knowledge of polyphosphate (polyP) synthesis in microalgae, enabling improved exploitation of their ability to sequester P from water sources and enhance recovery of a vital nutrient. Specifically, the mechanisms by which environmental conditions influence luxury uptake and potential species differences need to be studied to better understand observations at the population level and make informed decisions in the design of treatment processes. The experimental work was therefore divided into two main objectives: Objective 1 sought to determine whether there were in fact differences in luxury uptake ‘abilities’ between species. In Chapter 3, this is explored through the use of genetic database searches, biochemical assays, and protein modelling. Objective 2 examined the effects of environmental factors known to influence luxury uptake. In Chapter 4, the responses of the microalgae Chlamydomonas reinhardtii and Chlorella vulgaris to P repletion were studied in a range of conditions to identify similarities and differences in environmental influences. Chapter 5 sought to determine whether the observed differences could be due to responses at the genetic level, by comparing the gene expression levels of P-related genes in C. reinhardtii under selected sets of conditions from the previous chapter. An additional experiment was conducted, to examine gene expression without inducing ‘noise’ through changes in growth conditions, and this is discussed in Chapter 6. Using protein sequence homology searches, phylogenetic tree generation, protein structure modelling, and biochemical assays (using the chlorophytes C. reinhardtii, C. vulgaris, Desmodesmus cf. armatus, Gonium pectorale, Pediastrum boryanum, and the cyanobacterium Microcystis aeruginosa), it was shown that the ability to store P as polyP is common among microalgae, as implied by the broad conservation of the polyP polymerase VTC4, but luxury uptake abilities vary between species. All six tested microalgae responded to P addition following a period of P depletion by accumulating P as granular polyP. Under the conditions tested, the total P assimilated over 24 hours was similar for five of the microalgae tested (2.6 – 3.6% P by dry weight) but C. vulgaris assimilated considerably less P (~1.2% P) than the others. The effects of environmental conditions on P uptake and polyP accumulation were assessed by triggering luxury uptake in C. vulgaris and C. reinhardtii in different conditions of light supply, temperature, and pH, with different P repletion doses following different P depletion times. P uptake and polyP accumulation were influenced by light supply, P depletion time, and P repletion dose in both microalgae but P dose had the strongest influence in C. reinhardtii versus light supply in C. vulgaris. PolyP was still accumulated by these two species in conditions suppressing growth and severely repressing metabolism (10 °C and darkness), evidencing that P uptake and polyP synthesis do not require light energy. The model alga C. reinhardtii was then used to evaluate, for the first time, whether the differences in P uptake and polyP accumulation observed with respect to differences in environmental conditions were associated with differences in gene expression. Although the genes assessed were downregulated (relative to controls) 24 hours after P repletion, as expected, in all experimental conditions, changing conditions at the start of the experiment also caused changes in gene expression in controls, making it hard to distinguish responses to P repletion from ‘global’ responses to changing conditions. Another experiment was therefore performed where temperature and light intensity were maintained constant before and after P repletion. The results confirmed that increased P repletion dose and P depletion time were associated with increased P uptake and polyP accumulation over 24 hours. The results evidenced the expected downregulation of PSR1, VTC4, VTCX, and PTB5 after 1 hour of P repletion, but this response was much more salient after 7 days of P depletion (compared to 3 days). Changes in gene expression were also associated with P repletion dose, but only after 7 days of P depletion. This showed that the response to P repletion is stronger after a longer P depletion time but the observed expression changes did not support the hypothesis that these changes were the reason for the higher observed P uptake and polyP accumulation. For the first time, it has been systematically shown that the ability to accumulate P as polyP is widespread among microalgae but that the kinetics of P accumulation vary between species and this species-dependence is influenced by environmental factors. These factors engender differences at the level of gene expression, involving both components of the VTC complex and phosphate transporters. However, the differences in P uptake and polyP accumulation may be better understood by investigating the structural differences and changes in activity of relevant proteins.
Keywords: Microalgae; Metabolism; Effect of light on; Effect of temperature on; Effect of chemicals on; Phosphorus; Polyphosphates; 400410 Wastewater treatment processes